1987
DOI: 10.3348/jkrs.1987.23.6.985
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the liver hemangioma

Abstract: 15 liver hemangiom as Irom 10 patients were stud ied by mangetic resonance imaging (MRI) w ith 2.0 Tesla superconductive magnet in order to eva luate the detectability 01 the mass by MRI and to ana lyze the optimal pulse sequence in hi gh lield magnet. Identical multislice/multiecho techniques were used in all pati ents obtained with T1-and T2 weighted spin echo using TR 500, 1500, 2000 msec and TE 30, 60, 90, 120 msec. MRI could detect liver hemangiomas in all cases. Hemangioma tended to have sharp margin, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The AFM images of ZnO nanoparticles deposited at room temperature on silicon and quartz substrates at a pressure of 80 Pa are shown in figure 3. Cho [45] produced ZnO nanoparticles and observed hexagonal crystal shapes at the substrate temperatures above 700 • C. Christoulakis et al [46] observed nanosphagetti-like structures deposited for longer periods of time when the thickness of their films increased to 200 nm. Thareja and Shukla [47] found ZnO nanoparticles which varied in shape from spherical to platelet-like structures after ablation in acetone.…”
Section: Discussionmentioning
confidence: 99%
“…The AFM images of ZnO nanoparticles deposited at room temperature on silicon and quartz substrates at a pressure of 80 Pa are shown in figure 3. Cho [45] produced ZnO nanoparticles and observed hexagonal crystal shapes at the substrate temperatures above 700 • C. Christoulakis et al [46] observed nanosphagetti-like structures deposited for longer periods of time when the thickness of their films increased to 200 nm. Thareja and Shukla [47] found ZnO nanoparticles which varied in shape from spherical to platelet-like structures after ablation in acetone.…”
Section: Discussionmentioning
confidence: 99%
“…3 shows the temperature evolution of PL spectra in ZnO nanocrystals embedded into polymeric matrix PMMA in the temperature range from 85 to 290 K. Analysis of the low-temperature PL in ZnO NCs and its comparison with PL in bulk ZnO permits to define the nature and characteristics of the recombination processes in the nanoscale ZnO crystals near the absorption edge. The PL spectra are characterized by intensive emission in the near-UV region and lower emission in the green region of spectrum (507 nm) connected with the presence of intrinsic defects [6,7]. The recombination processes in ZnO NCs differ from that in bulk ZnO mainly, because of the larger surface-to-volume ratio and, therefore, larger amount of defects on the surface.…”
Section: Optical Absorption Measurementsmentioning
confidence: 99%